Penanggulangan Komplikasi dalam Perawatan Restorasi Implan Tulang - Suhandi Sidjaja (Faculty of Dentistry, Universitas Indonesia, 2015)
Clinical complications of endosseous implants are the effects of mal-treatments including patient selection, treatment planning, clinical execution and patient cooperation. This prospective and retrospective study consists of 24 patients nine women and 15 men with a mean age of 46.7 (range 14 to 70 years), rehabilitized with 33 implant restorations during 1985 - 2000. Nine single implant restorations were supported with nine cylinder implants, eight free standing implant restorations were supported with 14 cylinder implants, one blade implant and one screw implant, 16 tooth implant restorations were supported with nine blade implants, four solid screw implants, four cylinder implants and 18 natural teeth. The result of the study identified 51 complications, four altered sensations, 12 implants disintegration, 21 screw-loosening, three screw fracture, one abutment fracture, five marginal bone lost, and five caries. A total of 12 implant were removed 21 implant restoration were survived after re-treatments. Complication is a consequence of a fast developement of dental implant. However, it is not always considered a failure. The important thing to overcome the problem is a correct identification of the complication which leads to a proper re-treatment.